Polymorphic, Benign, Nonepileptic, Paroxysmal, Infantile Movements (Fejerman Condition) - Fernández-Alvarez, Emilio (Journal of Pediatric Neurology, 2015)
Monosymptomatic, benign, sudden, and brief episodes of paroxysmal nonepileptic movements are quite common in infants. Their morphology is polymorphic. According to their predominant semiology, different terms are used. The most frequent are “benign myoclonus of early infancy” and “shuddering attacks”; other forms of these episodes have been reported with various denominations generating a confusing terminological scenario. We must consider two opposing arguments: we could think of these varied episodes as different processes or as different expressive varieties of the same process. This article supports the thesis that these phenomena are different expressions of the same nondisease condition and, moreover, proposes a new descriptive term for their identification: polymorphic, benign, nonepileptic, paroxysmal infantile movements or, alternatively, Fejerman condition (FC).
Keywords: benign myoclonus; shuddering; nonepileptic paroxysmal disorders; nondisease conditions; Fejerman condition; PoBeIM